Gender, Competition, and Performance: International Evidence - Li, Kai; Peng, Qiyuan; Shen, Rui; Wong, Gabriel (Journal of Financial and Quantitative Analysis, 2025)
Using a hand-collected sample of 18,269 equity analysts from 42 countries over the period of 2004 to 2019, we establish an intriguing negative association between a country’s institutional/economic development and its female share of equity analysts. We show that, in individualistic countries only, there is no gender gap in analyst forecast accuracy. We further show that female analysts are more skilled and more likely to drop out when underperforming in individualistic countries compared to peers in collectivistic countries. The evidence supports our hypothesis that the national cultural value of individualism encourages women to make career choices consistent with their general aversion to competition.